“Where do these terrible diseases and pestilences come from?”. Illness in the Roman World in Light of the Ecclesiastical History of Eusebius of Caesarea - Bralewski, Sławomir (Studia Ceranea, 2022)
Eusebius of Caesarea did not put diseases at the center of his introduction to Church History. He used them instrumentally to promote his theses. Therefore, he neither referred to the medical knowledge of that time nor did he conduct their scientific classification or description. Nevertheless, Eusebius’ account contains observations about the sick and their afflictions. The Bishop of Caesarea clearly distinguished between diseases suffered by individuals and those that plagued the masses. In addition, they can be divided into diseases of the body, diseases of the mind, and diseases of the soul. Eusebius treated disease as a tool in God’s hands, with the help of which He intervened in history for the benefit of Christians. For Eusebius, the best physician of the body and soul was Jesus Christ, who, with his miraculous power, healed all diseases, expelled unclean spirits and demons, and even raised the dead.